'Crimson Nectar' blows-up in boardroom: a case of building marketing policy of a new generation product. (20th January 2010) - Unknown
This case presents an approach of a brewery that tries to market the new generation non-alcoholic exotic fruit drinks made of fresh cherries under the brand name Crimson Nectar in the Latin American market in dramatically changing consumer behaviour. This case has been developed as a simulation exercise to demonstrate the boardroom intricacies in formulating the marketing policies for new products. The discussion is presented in a narrative way to demonstrate board meetings in a company. The case also focuses the conflicts faced by companies in developing marketing strategies in a competitive market environment.